The medieval soundscape of Évora from a 17th-century perspective - Henriques, Luís (2021)
Blog post for the "Cantum Mensurable" blog about the Medieval soundscape of Évora (Portugal), mostly focusing on its religious institutions, present in the writings of 17th-century Jesuits Manuel Fialho and Francisco da Fonseca.